A comprehensive review on the significant role of nitrous oxide in the transformation of nitrogen oxides during combustion - Liu, Songlin; Zhu, Wenkun (Journal of the Energy Institute, 2024)
The intricate process of nitrogen transformation during combustion is crucial for in both the generation and control of NOx emissions, underscoring its paramount significance in environmental protection. This study focuses on the phenomenon a secondary increase in NO during air-staged combustion, systematically analyzing and summarizing the formation, decomposition, and reduction mechanisms of N2O. An exhaustive review of the dynamic interconversion between N2O and NO reveals a detailed phenomenon governing their mutual transformation during air-staged combustion. The observed differences in N2O and NO emissions arise from the distinct variances in their reaction mechanisms, which are uniquely tailored to the specific conditions encountered. N2O is present in the high-temperature zone of pulverized coal combustion due to the conducive atmosphere in the main combustion and transition zones, the secondary increase in NO in the transition zone is attributed to the oxidation of N2O to NO under these specific conditions. However, the secondary increase in NO may be closely related to N2O during the air-stage combustion of natural gas, which needs to be further explored. This research serves as a valuable reference for newcomers to the field of NOx research.
CRIS-Team Scopus Importer:2024-07-12
Keywords: Clean combustion; N; Nitrogen chemistry; NO; NOx control

Diagnostic investigation of devolatilization, ignition, and flame fluctuation during laminar oxy-coal combustion - Yuan, Mengfan; Zhu, Wenkun; Wang, Zhuozhi; Guo, Yuting; Li, Gaoyang; Chen, Yongxin; Peng, Jiangbo; Sun, Rui (Energy, 2024)
The rapid development of measurement technology has created possibilities for the advancement of intelligent combustion diagnostics. The high-speed OH-PLIF was used to investigate homogeneous ignition and combustion characteristics of gas-solid two-phase flame in a laminar flow reactor of oxy-coal combustion. The primary focus is to investigate the physico-chemical processes of gas-solid interaction during the early stages of combustion. The image processing was employed to analyze the flame features and then obtain the ignition mechanism, OH distribution, species radiations, and fluctuation frequency. Results show that the homogeneous reaction dominates the ignition and volatile combustion at the early stages of oxy-coal flame. The ignition delay time and volatile burning time decrease with the increasing gas temperatures and oxygen concentrations. The fluctuation dominant frequency increases from 190.5 Hz to 243.2 Hz at the ambient temperature from 1200 to 1800 K. The dominant frequency stabilizes between 243.2 Hz and 243.5 Hz at the ambient temperature from 1500 to 1800 K. The dominant frequency undergoes a shift to a maximum limit of 243.5 Hz from 1200 to 1800 K. When the oxygen concentration increases from 20 % to 40 %, the dominant frequency continues to rise from 244.8 Hz to 268.7 Hz.
CRIS-Team Scopus Importer:2024-01-05
Keywords: Devolatilization; Flame fluctuation; Ignition; Oxy-coal combustion